Localization patterns of steroid and luteinizing hormone receptors in the corpus luteum of Nelore (Bos taurus indicus) cows throughout the estrous cycle - Martin, Ian [UNESP]; Rodrigues, Marcela Marcondes Pinto [UNESP]; Fujihara, Caroline Junko [UNESP]; Marques Filho, Wolff Camargo [UNESP]; Oba, Eunice [UNESP]; Laufer-Amorim, Renée [UNESP]; Ferreira, João Carlos Pinheiro [UNESP] (My University, 2013)
The aim of the present study was to detect progesterone receptors (A and B isoforms), α and β estrogen receptors, luteinizing hormone receptors and aromatase cytochrome P450 enzymes in the corpus luteum of Nelore (Bos taurus indicus) cows using immunohistochemistry. The estrous cycles of 16 Nelore cows were synchronized, and luteal samples were collected via an incision into the vaginal vault. Samples were collected during specific days of the estrous cycle (days 6, 10, 15 and 18) and 24. h after circulating progesterone dropped, after luteolysis had occurred. After each biopsy was taken, all animals were resynchronized so that each biopsy was performed during a different estrous cycle. Our results showed that the concentration of studied proteins vary throughout the bovine estrous cycle. The highest concentration of α and β estrogen receptors and the highest concentration of plasma progesterone were both observed on days 10 and 15 of the estrous cycle. The highest concentration of progesterone receptors was observed on days 6 and 10 of the estrous cycle, and the most intense immunostaining for cytochrome P450 aromatase enzymes was observed on day 10 of the estrous cycle. The highest score of cells with plasma membrane immunostaining for LH receptors was observed on day 15 of the estrous cycle. In conclusion, this study demonstrates the varying concentrations of specific proteins within the corpus luteum of Nelore cows during the estrous cycle. This finding suggests that these receptors and enzymes, and their interactions, are important in regulating luteal viability. © 2013 Elsevier B.V.
Keywords: Corpus luteum; Estrous cycle; Immunohistochemistry; Nelore; Steroid hormone receptors; Animalia; Bos indicus; Bos taurus; Bovinae